Radiation‐Triggered Chemokine‐Secreting Probiotics for Boron Neutron Capture Therapy Based Radioimmunotherapy - Yang Liu; Yuzhong Qian; Shaobo Huang; Bingbing Li; Yue Yu; Xiang Cheng; Chang Chen; Jiheng Wang; Maosong Yang; Lizheng Liang; Xiancai Meng; Zhigang Liu (Advanced Science, 2026)
ABSTRACT An ideal radioimmunotherapy eradicates primary tumors and drives immune clearance of residual or metastatic tumor cells, but its clinical translation is severely limited by systemic immune toxicity and the immunosuppressive tumor microenvironment (TME). Here, we constructed engineered Escherichia coli Nissle 1917 with a tannic acid‐mediated boronophenylalanine coating and a radiation‐responsive genetic circuit, enabling TME‐responsive boron delivery for boron neutron capture therapy (BNCT). BNCT‐mediated selective tumor killing spared intratumoral probiotics, whose integrated genetic circuit was triggered by the low‐level incidental radiation generated during the BNCT process, including γ‐rays, to drive CXCL10 production, forming a feedback loop to remodel the TME. This strategy achieved robust tumor eradication, inhibited distal tumor growth and post‐surgical metastasis in murine models, pioneering a BNCT‐based radioimmunotherapy modality.